Protective effects of lycopene in cancer, cardiovascular, and neurodegenerative diseases: An update on epidemiological and mechanistic perspectives. (May 2020) - Saini, Ramesh Kumar; Rengasamy, Kannan R.R.; Mahomoodally, Fawzi M.; Keum, Young-Soo
Graphical abstract: Abstract: Recent mechanistic and epidemiological studies have provided insights into health benefits of dietary lycopene to decrease the risk and complications associated with several chronic diseases such as cardiovascular diseases (CVD), obesity, type 2 diabetes, cancer, and neurodegenerative disorders. These chronic diseases are primarily associated with oxidative stress-induced systemic and low-grade chronic inflammation. Owing to its potent antioxidant properties, lycopene can potentially alleviate enhanced levels of proinflammatory mediators ( e.g., proinflammatory cytokines IL-8, -6, and -1, and oxidized phospholipids) and prevent NF-κB activation by modulating oxidative stress. Moreover, lycopene serves as a precursor for various oxidative cleavage products and metabolites including Apo-8'-, apo-10'-, and apo-12'-lycopenals that can interact with multiple transcription factors ( e.g., Nrf2, RARs, RXRs, and PPARs) to overexpress antioxidant and cytoprotective Phase II enzymes and other growth-stimulating proteins ( e.g., brain-derived neurotrophic factor (BDNF) for enhanced neuroprotection. These events altogether can protect the body from chronic inflammatory disorders. In the present review, the latest mechanistic development from cell and animal models and results of case-control, cohort, and randomized trials are discussed to support the protective part of lycopene in cancer, CVD, and neurodegenerative disorders. This review focuses on cellular and molecular events involved in protective effects of lycopene. Although molecular and cellular mechanisms involved in health-promoting activities of lycopene have been reported, no detailed mechanistic studies have been published. Hence, future studies should be conducted to elucidate the mechanistic role(s) of lycopene-derived oxidation products in modulating cellular signaling.